2019
DOI: 10.3177/jnsv.65.272
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Bowman-Birk Inhibitor and α-Tocopheryl Succinate on Prostate Cancer Stem-Like Cells

Abstract: The reoccurrence of androgen-dependent prostate cancer after anti-androgen therapy mainly depends on prostate cancer stem-like cells. To reduce the risk, it is important to delete the cancer stem-like cells. Furthermore, to induce differentiation of cancer stem-like cells is critical to abrogate stemness of the cells. Therefore, we tried to investigate a possibility on the establishment of a new effective therapy to eradicate the cancer stemlike cells via the induction of differentiation in this study. Prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…2B, there was a significant increase in sphere formation capability in LNCaP stem-like cells compared with LNCaP parental cells, and BBI treatment suppressed the sphere formation capacity in LNCaP stem-like cells with a statistical significance. Similarly with the above observation, our previous report indicated that LNCaP stem-like cells, but not LNCaP parental cells, could exhibit resistance to flutamide (Kaneko et al, 2019). In this study, we demonstrated that concomitant treatment with a fixed dose of BBI almost abolished this resistance with a flutamide induced dose-dependent reduction in cell viability in LNCaP stem-like cells (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2B, there was a significant increase in sphere formation capability in LNCaP stem-like cells compared with LNCaP parental cells, and BBI treatment suppressed the sphere formation capacity in LNCaP stem-like cells with a statistical significance. Similarly with the above observation, our previous report indicated that LNCaP stem-like cells, but not LNCaP parental cells, could exhibit resistance to flutamide (Kaneko et al, 2019). In this study, we demonstrated that concomitant treatment with a fixed dose of BBI almost abolished this resistance with a flutamide induced dose-dependent reduction in cell viability in LNCaP stem-like cells (Fig.…”
Section: Resultssupporting
confidence: 89%
“…We then investigated whether BBI reduced stemness and resistance to ADT in LNCaP stem-like cells. The treatment dose of BBI was fixed at 200 μg/mL, as the cell growth control effect of BBI on LNCaP reached a plateau at this dose in a prior study (Kaneko et al, 2019). The results obtained showed that the BBI treatment significantly suppressed the levels of three cancer stem cell markers (CD24, CD44, and CD133) and slightly reduced the levels of the two other markers (SOX2 and Oct3/4) (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…stem-like cells [146] Combination of BBI and α-tocopheryl succinate results in cell growth inhibition and induction of apoptosis. BBI at the concentration of 200 µg/mL.…”
Section: Lncap Cell Line and Lncapmentioning
confidence: 99%
“…Kaneko et al [146] demonstrated the capability of soybean BBI to reinforce cytotoxicity induced by α-tocopheryl succinate (TOS) mitocan. As compared with individual BBI and TOS treatments, the combined application of these both agents resulted in a significant decrease in cell viability of prostate cancer cells (LNCaP) and undifferentiated prostate stem-like cells, which are more resistant to chemotherapy.…”
Section: Putative Mechanisms Of Anticarcinogenic Activitymentioning
confidence: 99%